Analysis of race walking technique post-competitive period in a world athletics championship - Campana Bonilla, M. V.; Alsowayan, M. N. (ISBS Proceedings Archive (Michigan), 2022)
The purpose of this study was to analyse the kinematic variables of an elite race walker gait technique during the post-competitive period in a World Athletics Championship. The elite athlete performed three race walking gait technique tests in a laboratory using three competitive race walking paces. Data for the flight time, step length, step frequency, and speed for the tests was collected. The one-way ANOVA of the three tests did not show statistically significant differences in flight time, step length, step frequency, and speed. However, the findings of this study showed that the competitive race walking pace would influence race walking kinematic variables and the elite athlete`s gait technique.